1997
DOI: 10.1007/s001250050804
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin concentrations: gender differences and associations with metabolic risk factors for cardiovascular disease

Abstract: Obesity results from an imbalance between energy intake and expenditure. Furthermore, obesity has long been recognized to have detrimental effects on health including an increased risk of cardiovascular disease (CVD) [1]. In this regard, the recent cloning of the mouse (ob) and human (OB) obese genes and the characterization of its protein product, leptin [2], has been a breakthrough of potentially great importance for the understanding of the pathophysiology of obesity.Leptin has been shown to lower body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
66
5
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 46 publications
22
66
5
3
Order By: Relevance
“…As expected, the serum leptin level was significantly higher in women. Such a gender difference in serum leptin levels has been reported previously [14] . Leptin is exclusively expressed in adipose tissue and secreted from white adipose cells [15] .…”
Section: Discussionsupporting
confidence: 72%
“…As expected, the serum leptin level was significantly higher in women. Such a gender difference in serum leptin levels has been reported previously [14] . Leptin is exclusively expressed in adipose tissue and secreted from white adipose cells [15] .…”
Section: Discussionsupporting
confidence: 72%
“…21 In the present study, a gender difference in adipocyte size was found as women had Figure 1 Associations of abdominal fat cell weight (FCW; left panels) and femoral FCW (right panels), expressed in mg lipidacell, with plasma insulin (top panels) and leptin (bottom panels) concentrations in 63 men (black circles) and 42 women (white circles).…”
Section: Discussionmentioning
confidence: 51%
“…However, associations between femoral FCW and plasma insulin as well as leptin levels were only signi®cant in women. Since plasma leptin concentrations have not been reported to be associated with regional AT distribution, 21,26,54,55 we believe that the reduced AT accumulation in the femoral region in men may account for the absence of relationship found in our male subjects. Overall, our observations support the notion that fat cell size is an important correlate of leptinemia.…”
Section: Discussionmentioning
confidence: 63%
“…12,23 In the fasting status, insulin injection can increase ob mRNA to levels of fed controls, 12,13 which suggests leptin mRNA expression is up-regulated by insulin. 59 However, leptin expression does not change after shortterm caloric restriction 19 and there is no acute insulin effect (either with euglycemic clamps, insulin injection or post-prandially) on ob gene mRNA expression or plasma leptin concentrations. 16 ± 21 Levels of leptin are increased by insulin only after prolonged administration; 2,12 a result consistent with our ®ndings that elevated HbA1c, and not c-peptide or insulin, is associated with higher leptin levels.…”
Section: Discussionmentioning
confidence: 99%